The Lifeboat Ethics And Humanist Ethics: Similarities And Dissimilarities - Appiah-Sekyere, Paul (Advances in Social Sciences Research Journal, 2018)
Albeit both the Lifeboat ethics and Humanist ethics have similar sources, namely, reason and science, there are dissimilarities in their respective ethical values that outnumber the similarities. This study examines how two ethics that have similar sources can produce similar and dissimilar ethical values to the extent that the latteroutnumber the former.